Electronic nicotine delivery systems (ENDS) dependence among Texas Young Adults, 2014-2019: Increasing trajectory after the 2017 surge in vape pod popularity. (1st December 2022) - Loukas, Alexandra; Marti, C. Nathan; Harrell, Melissa B.; Pasch, Keryn E.; Wilkinson, Anna V.
Abstract: Introduction: Use of electronic nicotine delivery systems (ENDS) increased significantly after 2017. The increase is attributed to a surge in popularity of vape pods containing nicotine salts, which are high nicotine concentration ENDS that may heighten risk for dependence. However, little is known about changes in ENDS dependence before and after the 2017 surge. We examined the trajectory of ENDS dependence among young adults from 2014 to 2019. Methods: Participants were 1700 18–25-year-olds (57.6 % female) from 24 Texas colleges who reported past 30-day ENDS use in at least one of eight study waves. ENDS dependence was assessed at all waves with one item, use of ENDS within 30 min of waking. A discontinuous growth curve model was fit to test the hypothesis that the ENDS dependence trajectory would increase only after 2017, from 2018 to 2019. The model included socio-demographic and cigarette dependence covariates Results: The proportion of young adults reporting ENDS dependence ranged from 2.3 % in 2014 to 8.2 % in 2019. Results from the discontinuous growth curve model indicated that the ENDS dependence trajectory was flat from fall 2014 to spring 2017. However, the post-2017 trajectory, from spring 2018 to spring 2019, was positive and significant indicating that the proportion of young adults reporting ENDS dependence increased after 2017. Conclusions: The increase in ENDS dependence after 2017 likely resulted from the surge in popularity of vape pods containing nicotine salts. These vape pods are a disruptive technology that may result in more young adults developing nicotine dependence symptoms than do earlier generation devices. Highlights: No longitudinal studies track changes in ENDS dependence among young adults. We examined ENDS dependence from 2014 to 2019, capturing the surge in vape pod sales. ENDS dependence was consistent from 2014 to 2017, but increased from 2018 to 2019. The increase is likely due to the late 2017 surge in sales of vape pods with nicotine salts.